Impact of IOT on Different Business Sectors: Deep Analysis Trends after Pandemic - Likhitha. R; Kamsala Jagannathachari Shiva Shankar; Sunetra Chatterjee (International Journal of Engineering and Management Research, 2023)
The internet of things helps Humans work smarter, as well as gain complete control over their lives. In addition to offering smart devices to automate homes, IoT is essential to various businesses. IoT makes provisions for businesses with a real-time look into how their systems really work, delivering insights to every business about the performance of machines from start to end of every operation. IoT gives assistance to businesses to automation and reduces labor costs. It also chops down waste and improves service delivery, making it economical to manufacture & supply goods and services, as well as offering clearness in customer transactions. IoT is the most important technology in modern life, and it will only gain popularity as more companies recognize the potential of linked devices to keep them focused and active. In the future what are all the changes that humans can expect through the Internet on things through various activities and also in various sectors can be described in this. The future of human life is living together with digital technology and IoT.